Evolution of Surface morphology on Ion Sputtered of Some III-V (001) Semiconductors - Saeed, Salah. R. (Sulaimani Journal for Pure and Applied Sciences, 2014)
Surface patterning of some III-V (001) compounds, under ion irradiation, has been investigated by means of Atomic Force Microscopy. The III-V(001) surfaces were exposed by Ar+ beam with varying incident angles (from 0° to 80° off-normal) with energy 2.0 keV and fluence 8.8 x1016 ion/cm2 at room temperature. Depending on the ion incident angle and target materials, different kinds of nanostructures have been observed on the surfaces, such as nanocavities, nanodots and well-ordered ripples at the oblique incidence angle of irradiation. The orientation of the ripples has been found to be incident angle dependent and it elongates along the projection of the ion beam on the irradiated surface. The RMS roughness and wavelength of the developed nanostructures are dependent on the angle and type of material. The results have been discussed in terms of ballistic processes of sputtering and Bradley Harper theory for surface modifications.
Keywords: Surface patterning; Ion irradiation; Ripples; IIIV semiconducting compound; BHtheory; Atomic force microscopy